A REVIEW OF THE DEVELOPMENT PACIFIC WHITE SHRIMP (Litopenaeus vannamei) FARMING IN INDONESIA - Supono, Supono; Rivaie, Arief Rahman (Indonesian Aquaculture Journal, 2025)
Pacific white shrimp (Litopenaeus vannamei) cultivation in Indonesia has been carried out since the early 2000s with satisfactory results. This shrimp is able to replace the previously cultivated black tiger (Penaeus monodon), which experienced cultivation failure due to disease attacks. The pond construction used includes an earthen pond, a lining pond, and a concrete pond, which are equipped with paddlewheels as a source of dissolved oxygen. Pacific white shrimp are mostly cultivated using semi-intensive, intensive, and super-intensive systems, depending on technological input and stocking density. Semi-intensive stocking density is around 50 PL/m2, intensive 100 PL/m2, and super-intensive 500 PL/m2, with productivity of 10 tons/ha, 15 tons/ha, and 42 tons/ha, respectively. There are two types of harvests carried out by farmers in Indonesia, namely partial harvests and total harvests. The main aim of partial harvest is to reduce excessive shrimp biomass, as indicated by a decrease in dissolved oxygen content. Problems that often arise during the cultivation process are disease attacks such as white spots and infectious myonecrosis (IMN) caused by viruses, White Feces Syndrome (WFS)  and Acute Hepatopancreatic Necrosis Disease (AHPND) caused by Vibrio parahaemolitycus and Enterocytozoon hepatopenaei (EHP). To increase the productivity of whiteleg shrimp cultivation, the advice given is to minimize disease attacks, namely by installing several biosecurity devices, such as bird scaring devices (BSD), crab protection devices (CPD), and water filtration. In addition, the application of a recirculation aquaculture system, biofloc technology, aquamimicry and whiteleg shrimp cultivation at low salinity (inland) can be an alternative cultivation in the future.